Komparasi Sub Sektor Pangan Basis - Sitorus, Nurmely Violita; Sitepu, Indrawaty (Musamus University, 2019)
This study aims to determine the commodity of any fruits that become the base of each subdistrict in Karo Regency, what commodities have fast and competitive growth in each regency in Karo Regency, the commodity of fruits of any base become a priority to be developed in each sub-district in Karo Regency. The results showed that fruits commodity which became base in Karo Regency were avocado, orange, mango, sawo, durian, guava, papaya, banana, pineapple, passion fruit, rambutan, salak; Fruit commodities have rapid growth in Karo regency are: avocado, durian, banana, pineapple, papaya, passion fruit; Commodities of fruits that have competitiveness in Karo Regency are: bananas, avocados, pineapples, passion fruit, oranges; Fruit commodity base that become the main priority in Karo Regency based on a combination of the Location Quotient (LQ) approach, the Proportional Growth (PP) component and the Regional Share Growth (PPW) that is banana , avocado, pineapple, passion fruit. Keywords: Location Quotient; Shift Share; priority fruit; base sector; Karo District